Calibration of polarization effect of a high-numerical-aperture objective lens with Mueller matrix polarimetry. (21st December 2018) - Chen, Chao; Chen, Xiuguo; Gu, Honggang; Jiang, Hao; Zhang, Chuanwei; Liu, Shiyuan
Abstract: The calibration of the polarization effect of a high-numerical-aperture (high-NA) objective lens (OL) is of great significance for high-precision polarized light micro-imaging. In this work, we propose a method to calibrate the polarization effect of a high-NA OL with Mueller matrix polarimetry in a retro-reflection configuration by using a spherical mirror as the reference sample. We present the calibration details in both the conoscopic and orthoscopic illumination modes. A high-NA OL with a NA of 0.95 is exemplified to demonstrate the capability of the proposed calibration method, and the experiments performed on two standard SiO2 /Si thin film samples with thicknesses of 25 nm and 100 nm verify the calibrated results. Compared with the existing calibration methods, the proposed method is simpler and more efficient for implementation, and moreover, the calibrated Mueller matrices contain all the polarization information of the high-NA OL under test. It is therefore expected that the proposed calibration method could provide a more complete polarization characterization of the high-NA OL.